FUNGSI ADMINISTRASI KEUANGAN DALAM MENGURANGI KETIDAKTEPATAN PEMBUKUAN PADA WARKOP RENCONG KUPI DI KOTA MEDAN - Tengku Dhika Syaiful Husni K.; Christy Hartagracea Sinaga; Exi Octavia Sitohang (Prodi Pendidikan Administrasi Perkantoran UNIMED, 2024)
This study aims to determine the role of financial administration functions in reducing bookkeeping inaccuracies at Warkop Rencong Kupi in Medan City. The research used a quantitative method with data collected through observation, interviews, questionnaires, and documentation. The population included the owner, employees, and regular customers involved in financial transactions. The findings indicate that the implementation of financial administration functions—planning, organizing, actuating, and controlling—significantly reduces bookkeeping errors. A well-managed financial administration system helps maintain accurate financial records, improves accountability, and facilitates decision-making. Therefore, the effective application of financial administration functions enhances financial management efficiency and supports the sustainability of small businesses such as Warkop Rencong Kupi.